The Influence of Celebrity Endorser and Online Promotion on Purchase Decision Through Brand Image - Lestari, Mulianda; Wahyono, Wahyono (Management Analysis Journal, 2021)
The purpose of this study was to determine whether celebrity endorsers, brand image and online promotion had an effect on purchasing decisions, and to determine whether brand image is able to mediate celebrity endorsers and online promotion on purchasing decisions. The population data in this research is consumers of Mustika Ratu cosmetic products in Semarang City. The total sample is 115 respondents. This research using the incidental sampling technique. The data analysis method in this research using descriptive analysis, regression analysis, and path analysis with IBM SPSS version 20. The research result shows that celebrity endorser, online promotion and brand image had positive and significant influence on purchasing desicion. Brand image are also able to mediate the effect of celebrity endorser and online promotion toward purchasing desicion. The suggestion givento pay more attention to the selection of celebrity endorsers an effort to increase purchasing decisions. For further researchers, it is expected to conduct research with the same aspects in different areas the consistency of this research can be tested.